Computational Analysis of Heat Transfer & Flow Characteristics of Swirl Flow Jet Implement - Rajendran S., Arul Murugan M., Thirupathiraja S., Karunakaran N., Karthikeyan P., Sam Prasanna J., Boopalan J., Chokkalingam V. (International Journal of Advanced Science and Technology, 2020)
Impinging jets have been widely used for increasing heat transfer in engineering applications such as cooling of hot steel plates and turbine blades, tempering of glass, drying of papers and films and cooling of electronic components In the last decades, the semiconductor industry developed so rapidly that the size of electronic component has become less and less. This trend results in the increase of power density, and the simultaneous increase of heat flux on the apparatus. As most of the electronic chips operate only in some range of temperature, it is very important to accelerate the heat dissipation of electronic components. It is obviously that the traditional natural and forced convection methods can’t satisfy the cooling of such high heat flux density. In this situation, the swirling jet impingement gets more and more attention as a very potential alternative because of its much better heat transfer effect than the other methods. The objective of the study is to investigate the characteristics of the heat transfer for swirling jet impingement on a surface which aims to enhance the heat transfer rate and also to compare heat transfer characteristics of straight Impinging jet and swirl flow impinging jet. The present study focuses on the verification of the swirling jet effect on the distribution of the local heat transfer coefficient on the impinged target surface. Studies would be conducted for a wide range of parameters including Reynolds Number, jet impingement angle, swirl Pitch and nozzle to target plane spacing. The motivation of the present work is to explore the efficiency of swirling jet impingement cooling and understand the mechanisms by which heat is removed from a constant heat flux surface.